2017
DOI: 10.1109/tvcg.2016.2598448
|View full text |Cite
|
Sign up to set email alerts
|

Hairy Slices: Evaluating the Perceptual Effectiveness of Cutting Plane Glyphs for 3D Vector Fields

Abstract: Three-dimensional vector fields are common datasets throughout the sciences. Visualizing these fields is inherently difficult due to issues such as visual clutter and self-occlusion. Cutting planes are often used to overcome these issues by presenting more manageable slices of data. The existing literature provides many techniques for visualizing the flow through these cutting planes; however, there is a lack of empirical studies focused on the underlying perceptual cues that make popular techniques successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Pilot testing indicated that the two streamlet conditions would benefit from additional seeds, and the seeding density was increased to 40×40 (a four‐times increase), as can be seen in Figures 2a and 2b. This increase of seed density is supported by the results of our prior work [SBW16], which found that thin glyph geometries could be successfully seeded at higher densities than thicker geometries without a reduction in perceptual performance.…”
Section: Methodssupporting
confidence: 73%
See 4 more Smart Citations
“…Pilot testing indicated that the two streamlet conditions would benefit from additional seeds, and the seeding density was increased to 40×40 (a four‐times increase), as can be seen in Figures 2a and 2b. This increase of seed density is supported by the results of our prior work [SBW16], which found that thin glyph geometries could be successfully seeded at higher densities than thicker geometries without a reduction in perceptual performance.…”
Section: Methodssupporting
confidence: 73%
“…In general, the method and experimental design follows those described in the previous paper [SBW16], with some improvements.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations